An Online Review of Plastic Surgeons in Southern California. (May 2015) - Lewis, Priya; Kobayashi, Emily; Gupta, Subhas
Abstract : Background: It has become commonplace for patients to access online reviews of physicians when making choices about health care, just as any consumer would in today's computer-dependent world. Previous studies have shown that online reviews of physicians are generally positive. However, 1 negative review has the potential to adversely affect business and reputations. Objectives: To characterize the online presence of plastic surgeons in Southern California as portrayed by physician rating websites (PRWs). Methods: An extensive online database of board-certified plastic surgeons was used to generate a list of surgeons within a 50-mile radius of Pomona, CA. Ratings from the PRWs HealthGrades.com, Vitals.com, and UCompareHealthcare.com were cataloged by number of reviews and ratings. Results: Two hundred sixty-three surgeons were evaluated with the most-represented cities being Beverly Hills (N = 47), Los Angeles (N = 31), and Newport Beach (N = 27). Ninety-seven percent of the surgeons were rated on at least 1 of the 3 PRWs chosen. In general, surgeons were rated highly, with a mean rating of 85%, SD, 14% ( P < 0.01), with a mean of 11.0 ratings per PRW, SD 10.9 ( P < 0.01). Total online ratings ranged from 0 to 222 per surgeon. The median number of total reviews was 25 and the mean rating for those surgeons above and below the median were equivocal, at 86% and 85%, respectively ( P = 0.284). Conclusions: In this study, we found that plastic surgeons in Southern California have an online presence that can be influenced by their patients; they should be aware of this and conscious of their online reputations. Overall, the ratings were high, regardless of the number of reviews.